2016
DOI: 10.1080/01904167.2016.1170851
|View full text |Cite
|
Sign up to set email alerts
|

Differential cadmium stress tolerance in wheat genotypes under mycorrhizal association

Abstract: Arbuscular mycorrhizal (AM) fungi display efficient association with the land plants and is known to protect plants against various abiotic stresses including heavy metal stress. This work reports the synergistic effects of natural genotypic variation and AM association in cadmium (Cd) stress alleviation. Two genotypes of wheat viz. RAJ 4161 (resistant) and PBW 343 (sensitive) were subjected to different concentrations of Cd (0, 100, 200 and 300 mg Cd kg 1 soil) for 30 days. Cd application resulted in increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 40 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The concentration of catalase was reported higher in the textile treated plant both in roots and leaves as compared to the plant under well watered conditions. This is in conformity with result reported for Triticum aestivum (24). A result of increased catalase activity had also been found under stress in Brassica juncea (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of catalase was reported higher in the textile treated plant both in roots and leaves as compared to the plant under well watered conditions. This is in conformity with result reported for Triticum aestivum (24). A result of increased catalase activity had also been found under stress in Brassica juncea (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Besides, AMF reduces the uptake of Cd and regulates its distribution between shoots and roots (Chen et al, 2005; Chen et al, 2019). Previous studies have shown that AMF can increase the biomass of host plants, such as maize (Gu et al, 2019), trigonella (Abdelhameed & Metwally, 2019), and wheat (Sharma et al, 2016), by effectively alleviating the Cd damage to the plants. AMF also induces the expression of phosphate transporter mRNA and affects the growth of maize under Cd stress (Gu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The use of arbuscular mycorrhizal fungi is an alternative to help increase plant growth and to inhibit the translocation of heavy metals to shoots (Sharma et al 2016;Ishaq 2018), increase nutrient uptake (Riaz et al 2021), bind toxic metal (Joner et al 2004), immobilize heavy metals in plant roots or phytostabilization (Ambrosini et al 2015;Wu et al 2016) acts as a filter to block xenobiotics in its mycelium (Wu et al 2019). Therefore, mycorrhizae act as a physical barrier and serve as an envelope for the host (Ma et al 2019).…”
Section: Introductionmentioning
confidence: 99%